Physical activity and mental health among undergraduate students - Elliot, Catherine, author; Anderson, Sharon, advisor; Kennedy, Catherine, advisor; Morgan, George, committee member; Butki, Brian, committee member (Colorado State University. Libraries, 2010)
This study was conducted to analyze possible influences of physical activity level, student group, and/or gender on seven mental health variables related to depression in undergraduate students. A campus health initiative. Healthy Campus 2010, set goals of increasing the number of students who are physically active three days per week to 55% and decreasing suicide attempts by 2010. Focusing on undergraduate students, the goal of this research was to replicate previous research efforts that linked physical activity levels with mental health related to depression. The national sample included a random selection of 2,146 students from the reference group of 61,758 college students enrolled as undergraduate students who completed the spring 2007 National College Health Assessment (NCHA). Colorado State University (CSU) participants served as a comparison group to the NCHA reference group. The analysis included seven 4 x 2 x 2 three-way ANOVAs to discover relationships between the seven mental health variables that related to depression (felt hopeless, felt overwhelmed, felt exhausted, felt very sad, felt depressed, considered attempting suicide, and attempted suicide) and the three independent variables, physical activity level (0 days, 1-2 days, 3-4 days, and 5-7 days), student group (NCHA reference group and CSU), and gender. There were relationships between the five variables that reflected mild mental health issues and physical activity levels, with small effect sizes. As the physical activity levels increased, students reported better mental health related to depression. There was one significant interaction between student group and physical activity level on the felt exhausted variable. There was a relationship between variables reflecting mild mental health and gender. Males reported better depression related mental health, with small to typical effect sizes {d = .20-.49). However, the contemplating suicide and attempting suicide variables were not significantly related to gender or physical activity levels. Overall, these data support current research by showing similarities between college students and other demographic groups. Physical activity and gender have shown correlations with mental health. These implications may influence college health services to use an integrated care system, merging mental health with medical services.
Covers not scanned.
Keywords: Exercise -- Psychological aspects; College students -- Psychology; Depression, Mental